Aquatic Colloidal Graphene Gel Polymer Electrolyte for Flexible Rechargeable Zinc Air Batteries. Issue 12 (1st December 2022) - Jia, Xingliang; Ma, Jingling; Zhang, Liangliang; Zhang, Chenfei; Wang, Guangxin
Abstract : An alkaline gel polymer electrolyte, namely a poly (acrylic acid)-zinc acetate (Zn(AC)2 )-aquatic colloidal graphene (ACG) solution (PAA-Zn(AC)2 -ACG), was prepared by solution casting method. Properties of PAA-Zn(AC)2 -ACG were studied by Fourier transform infrared spectrometer (FTIR), scanning electron microscopy (SEM), AC impedance, cyclic voltammetry (CV) and water retention ability. Results obtained show that PAA-Zn(AC)2 -ACG exhibits a high ionic conductivity of 407.9 mS·cm –1, an electrochemical stability window of 1.7 V, and 72.5% water retention ability. Flexible zinc-air batteries (ZABs) with PAA-Zn(AC)2 -ACG gel polymer electrolyte have an better discharge capacity of 672 mAh g −1 Zn at 0.5 mA·cm –2 (current density), a continuous charge-discharge duration of 43.3 h, 130 cycles, and a cycle efficiency of 64.8%. Based on work done in this study, it can be concluded that flexible ZABs have advantageous prospects and large potential for practical applications.